Dust properties across the CO snowline in the HD 163296 disk from ALMA and VLA observations - Guidi, Greta; Dullemond, Cornelis (Arxiv, 2016)
To characterize the mechanisms of planet formation it is crucial to investigate the properties and evolution of protoplanetary disks around young stars, where the initial conditions for the growth of planets are set. Our goal is to study grain growth in the disk of the young, intermediate mass star HD163296 where dust processing has already been observed, and to look for evidence of growth by ice condensation across the CO snowline, already identified in this disk with ALMA. Under the hypothesis of optically thin emission we compare images at different wavelengths from ALMA and VLA to measure the opacity spectral index across the disk and thus the maximum grain size. We also use a Bayesian tool based on a two-layer disk model to fit the observations and constrain the dust surface density. The measurements of the opacity spectral index indicate the presence of large grains and pebbles ($\ge